Pengaruh Penerapan Model Pembelajaran Discovery Learning Berbantuan Media Permainan “Finding Me” terhadap Minat Belajar Peserta Didik Kelas IV di Gugus III Labuapi - Nurul Latifah; Darmiany; Aisa Nikmah Rahmatih (Mataram University, 2026)
This study aimed to determine the effect of the Discovery Learning model assisted by the Finding Me game media on the learning interest of fourth-grade students in IPAS subjects at Cluster III, Labuapi District. Based on preliminary observations, students were still less active in learning activities and their initial abilities were still at an average score of 60, so a more engaging and interactive learning model was needed. This study used a quantitative approach with an experimental method and a pretest-posttest control group design. The research was conducted at SDN 1 Bajur as the experimental class with 34 students and SDN 3 Bajur as the control class with 31 students, resulting in a total sample of 65 students. Data collection techniques included observation, questionnaires, documentation, as well as pretest and posttest. Data were analyzed using normality tests, homogeneity tests, N-Gain tests, and t-tests. The results showed that students’ learning interest reached 88.12% in the very good category. The attention indicator obtained 81%, feeling happy 81.61%, interest 81.47%, and active participation 82.79%. Teacher observation results reached 87.5% and student observations reached 83.3%, both categorized as very good. These results indicate that the Discovery Learning model assisted by the Finding Me game media was able to create active, interactive, and enjoyable learning so that students became more focused, enthusiastic, and involved during the learning process. Students’ learning outcomes in this study were only used as supporting and comparative data. The t-test result obtained a significance value of 0.601 (>0.05), indicating no significant difference in students’ learning outcomes. Therefore, the Discovery Learning model assisted by the Finding Me game media proved to be more effective in improving students’ learning interest in elementary school IPAS learning.